Sistem Pakar Untuk Mendiagnosa Infeksi Mikroorganisme Pada Anak Menggunakan Metode Forward Chaining - William Tupan; Djoni Haryadi Setiabudi; Andreas Handojo (Universitas Kristen Petra, 2022)
Infectious diseases caused by microorganisms such as viruses, bacteria, fungi, and worms are very vulnerable to attack children, this is caused by a lack of self-awareness to maintain personal and environmental hygiene and the immune system that exists in children's bodies that have not been fully developed. Lack of knowledge makes parents also unable to recognize the symptoms of diseases suffered by children that arise due to infection with these microorganisms.This expert system was created to diagnose diseases in children caused by microorganisms such as viruses, bacteria, fungi, and worms. From this expert system information can be obtained about the name of the disease, how to handle it and the level of confidence in the diagnosis. This expert system uses the Forward Chaining method and the Certainty Factor method.The results of this system test show that the system is able to determine the disease, how to handle it, and is able to display the level of confidence in the system diagnosis, based on the symptoms previously selected by the user.